Pengembangan Perkalian Wordwall Berbasis Website Pada Mata Pelajaran Matematika Kelas II SD Negeri Grogol 2 Depok - Meilani, Sarah; Ritonga, Rudi (Academy of Education Journal, 2025)
This research uses a website-based wordwall learning model, a technology-based learning model that utilizes touchscreen technology as the primary medium in the teaching and learning process. The objectives of this research are: 1) To explain the steps for developing a website-based multiplication wordwall for second-grade mathematics at SD Negeri Grogol 2 Depok, 2) To describe the validation of the website-based multiplication wordwall for second-grade mathematics at SD Negeri Grogol 2 Depok, and 3) To describe the effectiveness of the website-based multiplication wordwall for second-grade mathematics at SD Negeri Grogol 2 Depok. This research was conducted using the Research and Development (R&D) method, implemented over two cycles, one on a small scale and one on a large scale, using the Dick and Carey Model. The results of this study indicate that in cycle 1, student learning outcomes in multiplication increased by 85%, categorized as sufficient. The average score was only 85 out of all students' scores. Meanwhile, in cycle II, the implementation of the website-based wordwall media achieved a 90% improvement, categorized as very high. The average student learning achievement for cycle II was achieved. Based on these two cycles, it can be concluded that the implementation of the website-based wordwall media in Mathematics, particularly in the Multiplication subject, can improve student learning outcomes in Grade 2 of SDN Grogol 2 Depok.